Pectic substances from babassu mesocarp flour: extraction and characterization - Jaine Oliveira; Yves José Souza Santos; Cleber Amaral Mafessoni Liviz; Gisele Teixeira de Souza; Ladyslene Chrístyns de Paula; Luís Fernando Polesi; Gabrieli Oliveira Folador (The Journal of Engineering and Exact Sciences)
The Amazon region contains distinct fruit species, such as the babassu, which are still little known, but may have great scientific and technological potential. Oil and flour are extracted from babassu fruits. The oil is used industrially and is listed in the Codex Alimentarius as a commodity. Babassu mesocarp flour is consumed in the Amazon region but is little known technologically. For this purpose, the present work aimed to use babassu mesocarp flour to extract pectin, an important additive for the food industry. The yield was quantified and the titration quality of the extracted material was evaluated. In order to determine the best extraction conditions, were tested different extraction time (30, 60 and 90 min) and concentration of citric acid (3, 4.5 and 6%) at constant temperature (90°C). The best results of quality were found for Experiment 5. Yield was approximately 25% when operating conditions were 60 min and 4.5% citric acid. Titrimetric quality of pectic material extracted in these conditions (experiment 5) was better than the others, with highest concentration of galacturonic acids (50%) and the highest degree of esterification (71.4%). Results of this study showed that mesocarp of a fruit from the amazon region (babassu) proved to be a great alternative source for pectic substances extraction. Technological quality of its pectic substances still needs to be better evaluated.